(untitled) (CIPEEX, 2022)
CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) HAS SEVERAL CONSEQUENCES, ONE OF THE MOST IMPORTANT BEING THE DEPRECIATION OF SKELETAL MUSCLE ACTIVITY. THE PRESENT WORK AIMS AT UNDERSTANDING HOW COPD AFFECTS THIS MUSCLE AND DISCUSSES SOME POSSIBLE WAYS TO MINIMIZE THESE EFFECTS. THE METHODOLOGY USED WAS THE RESEARCH IN THE SCIELO, PUBMED AND GOOGLE ACADEMIC DATABASES OF ORIGINAL SCIENTIFIC PAPERS AND LITERATURE REVIEWS BETWEEN THE YEARS 2014 AND 2018. THE RESULTS INDICATE A HIGH INDEX OF ATROPHY, MAINLY THROUGH THE MYOSTATIN PATHWAY, AFFECTING SIGNIFICANTLY THE MORPHOLOGY OF THE FIBERS, BESIDES A NOTORIOUS OXIDATIVE STRESS AND REDUCED DIAMETER OF THE FIBERS, WHICH INTERFERES IN ITS CAPACITY OF CONTRACTION. WITH THIS, IT IS CONCLUDED THAT COPD ACTS ON SKELETAL MUSCLE DYSFUNCTION THROUGH SEVERAL MECHANISMS, WHICH HAVE SEVERE CONSEQUENCES THAT MAY POSSIBLY BE TREATED WITH REGULAR PHYSICAL ACTIVITIES AND SOME PHARMACOLOGICAL SUBSTANCES.